Epistemic injustice in academic global health. Issue 10 (October 2021) - Bhakuni, Himani; Abimbola, Seye
Summary: This Viewpoint calls attention to the pervasive wrongs related to knowledge production, use, and circulation in global health, many of which are taken for granted. We argue that common practices in academic global health (eg, authorship practices, research partnerships, academic writing, editorial practices, sensemaking practices, and the choice of audience or research framing, questions, and methods) are peppered with epistemic wrongs that lead to or exacerbate epistemic injustice. We describe two forms of epistemic wrongs, credibility deficit and interpretive marginalisation, which stem from structural exclusion of marginalised producers and recipients of knowledge. We then illustrate these forms of epistemic wrongs using examples of common practices in academic global health, and show how these wrongs are linked to the pose (or positionality) and the gaze (or audience) of producers of knowledge. The epistemic injustice framework shown in this Viewpoint can help to surface, detect, communicate, make sense of, avoid, and potentially undo unfair knowledge practices in global health that are inflicted upon people in their capacity as knowers, and as producers and recipients of knowledge, owing to structural prejudices in the processes involved in knowledge production, use, and circulation in global health.